KEBIJAKAN PERMENPAN DAN RB RI NO. 26 TAHUN 2016 TENTANG PENGANGKATAN PNS DALAM JABFUNG MELALUI PENYESUAIAN/INPASSING TERKAIT JABFUNG PUSTAKAWAN - Supriyanto Supriyanto (Jurnal IPI (Ikatan Pustakawan Indonesia), 2017)
Librarian are recognized as legitimate professional (functional position) in the government.That is professionalism with future prospects for those who have certain skills in the field of "librarianship". Librarian activities include library management, library services, and the development of librarian systems, supported with the foundation of professionalism and professional ethics.When the role of librarians is limited, both quality and quantity, MENPAN and RB RI Regulation Number 26 of 2016 on the Appointment of Civil Servants in Functional Positions Through Adjustment / Inpassing published. Formation of librarian positions opened wide by sticking to the rules of professionalism to maintain the sustainability of tasks and functions.